Effects of perineal massage during childbirth on maternal and neonatal outcomes in primiparous women: A systematic review and meta-analysis. (February 2023) - Li, Yuxuan; Wang, Chongkun; Lu, Hong; Cao, Linlin; Zhu, Xiu; Wang, Aihua; Sun, Ruiyang
Abstract: Background: Perineal massage during childbirth has been recommended as an effective measure to prevent perineal injury. However, the overall effects of perineal massage during childbirth on maternal and neonatal outcomes in primiparous women remain inconclusive. Particularly, the effects of perineal massage begun during different stages of labor need to be further investigated. Objectives: To comprehensively review the effects of perineal massage during childbirth on primiparous health outcomes, including perineal-related outcomes, duration of labor, hemorrhage and postpartum perineal pain, and neonatal outcomes, including Apgar scores and neonatal complications, and to further explore the effects of perineal massage begun during different stages of labor. Design: A systematic review and meta-analysis following the Cochrane Handbook guidelines and PRISMA2020 . Methods: A systematic search strategy was developed following the three-phase search approach, and the literature search was conducted in electronic databases and clinical trial registers from inception to 7th January 2022. Study selection and data extraction were completed independently by two researchers. The updated Cochrane risk of bias 2.0 tool for randomized trials was chosen to evaluate the quality of included studies. Data analyses were conducted using the Revman5.4 software, and subgroup analyses were performed based on the different start times of perineal massage. Furthermore, the certainty of body of evidence for each outcome was assessed utilizing the GRADEpro online tool. Results: Seventeen randomized controlled trials involving 3248 primiparous women were included in the review. The pooled results of meta-analyses indicated that perineal massage begun during the second stage of labor significantly increased the occurrence of intact perineum (RR = 2.78, 95 % CI: [1.52, 5.05], P < 0.001), reduced the rate of second- and third-degree perineal lacerations ( P < 0.05), and decreased the incidence of episiotomy (RR = 0.63, 95 % CI: [0.50, 0.79], P < 0.001), while perineal massage during the first stage of labor effectively shortened the duration of the first and second stages of labor ( P < 0.05). The available evidence also suggests the potential role of perineal massage on hemorrhage and long-term postpartum perineal pain ( P < 0.05). However, the aggregated results failed to demonstrate the beneficial effects of perineal massage on neonatal outcomes ( P > 0.05). Conclusions: Perineal massage begun during the second stage of labor effectively improves the perineal-related outcomes in primiparous women, while perineal massage during the first stage of labor significantly shortens the duration of labor. High-quality studies exploring the standardized procedure for perineal massage and the short- and long-term effects of perineal massage are warranted. Registration number: CRD42022302336 (PROSPERO).